Simultaneous Determination of Salicylic Acid, Jasmonic Acid, Methyl Salicylate, and Methyl Jasmonate from Ulmus pumila Leaves by GC-MS - Zhi-hong Huang; Zhi-li Wang; Bao-lin Shi; Dong Wei; Jian-xin Chen; Su-li Wang; Bao-jia Gao (International Journal of Analytical Chemistry)
Salicylic acid, jasmonic acid, methyl salicylate, and methyl jasmonate are important phytohormones and defensive signaling compounds, so it is of great importance to determine their levels rapidly and accurately. The study uses Ulmus pumila leaves infected by Tetraneura akinire Sasaki at different stages as materials; after extraction with 80% methanol and ethyl acetate and purification with primary secondary amine (PSA) and graphitized carbon blacks (GCB), the contents of signal compounds salicylic acid, jasmonic acid, methyl salicylate, and methyl jasmonate were determined by GC-MS. The results showed that the level of salicylic acid, jasmonic acid, methyl salicylate, and methyl jasmonate increased remarkably in U. pumila once infected by T. akinire Sasaki, but the maximums of these four compounds occurred at different times. Salicylic acid level reached the highest at the early stage, and jasmonic acid level went to the maximum in the middle stage; by contrast, change of content of methyl salicylate and methyl jasmonate was the quite opposite.